Pembelajaran Matematika dengan Model Reciprocal Teaching Untuk Melatih Kecakapan Akademik Siswa Kelas VIII SMP - Muslimin; Indaryanti; Susanti, Ely (Mathematics Education Journal, 2017)
The research is aims to describe the level of a student's academic proficiency in mathematics learning cooperative model of reciprocal teaching. Subjects in this study were students VIII.5 SMP Negeri 1 Indralaya totaling 36 people. Data collected through observation and tests. Based on the analysis of observational data show the average score of their academic ability of students is 85.26 and classified in the high category. The average score of student learning outcomes is 83.01 and classified in the high category. In connection with these conclusions, the math teachers should be able to apply reciprocal teaching models in order to train the student's academic skills.